Women with a low-satiety phenotype show impaired appetite control and greater resistance to weight loss. Issue 8 (28th October 2019) - Buckland, Nicola J.; Camidge, Diana; Croden, Fiona; Myers, Anna; Lavin, Jacquelynne H.; Stubbs, R. James; Blundell, John E.; Finlayson, Graham
Abstract: This trial compared weight loss outcomes over 14 weeks in women showing low- or high-satiety responsiveness (low- or high-satiety phenotype (LSP, HSP)) measured by a standardised protocol. Food preferences and energy intake (EI) after low and high energy-density (LED, HED) meals were also assessed. Ninety-six women ( n 52 analysed; 41·24 (SD 12·54) years; 34·02 (sd 3·58) kg/m 2 ) engaged in one of two weight loss programmes underwent LED and HED laboratory test days during weeks 3 and 12. Preferences for LED and HED food (Leeds Food Preference Questionnaire) and ad libitum evening meal and snack EI were assessed in response to equienergetic LED and HED breakfasts and lunches. Weekly questionnaires assessed control over eating and ease of adherence to the programme. Satiety quotients based on subjective fullness ratings post LED and HED breakfasts determined LSP ( n 26) and HSP ( n 26) by tertile splits. Results showed that the LSP lost less weight and had smaller reductions in waist circumference compared with HSP. The LSP showed greater preferences for HED foods, and under HED conditions, consumed more snacks (kJ) compared with HSP. Snack EI did not differ under LED conditions. LSP reported less control over eating and reported more difficulty with programme adherence. In conclusion, low-satiety responsiveness is detrimental for weight loss. LED meals can improve self-regulation of EI in the LSP, which may be beneficial for longer-term weight control.